Liver cyst infection in kidney transplant patient with autosomal dominant polycystic kidney disease: Interest of PET/CT in diagnosis and treatment - H, Georgery; G, Migali; JM, Pochet; M, Tintillier; C, Van Ende; C, Cuvelier (Journal of Clinical Nephrology, 2018)
Liver cyst infection in patients with autosomal dominant polycystic kidney disease (ADPKD) is a rare but life-threatening complication. Diagnosis and treatment remain challenging. We report the case of a 64-year-old kidney transplant patient presenting with fever and abdominal pain. The diagnosis of liver cyst infection was made by positron emission tomography scan (PET/CT). Moreover, the course of our patient illustrates the interest of subsequent PET/CT during follow-up as our patient failed on antibiotherapy and required liver cyst drainage.